2017
DOI: 10.1016/j.clnesp.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition-associated cholestasis and triglyceridemia in surgical term and near-term neonates: A pilot randomized controlled trial of two mixed intravenous lipid emulsions

Abstract: s u m m a r yBackground: Cholestasis is a common complication in infants receiving prolonged parenteral nutrition (PN). We studied the effects of two intravenous lipid emulsions composed with either 30% soybean oil, 30% medium-chain triglycerides (MCT), 25% olive oil, and 15% fish oil (SMOF) or with 50% MCT and 50% soybean oil n-6 (MCT/SOY) on the incidence of cholestasis in surgical term and near-term neonates. Methods: A single-center, double-blinded, randomized controlled trial compared the incidence of cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…Literature evaluating the role of ILEs in the prevention of cholestasis specifically in IF patients is limited and somewhat conflicting. In a recent randomized controlled trial, neonates receiving SMOF after gastrointestinal surgery did not have higher liver enzymes or incidence of cholestasis than neonates receiving a 50% soybean based emulsion [17]. Alternatively, in a randomized controlled trial of infants in China following intestinal surgery, infants receiving SMOF for 4 weeks had lower liver enzymes and direct bilirubin but no difference in weight gain or sepsis episodes compared to patients receiving a mediumchain triglyceride/long-chain triglyceride emulsion [18].…”
Section: Discussionmentioning
confidence: 96%
“…Literature evaluating the role of ILEs in the prevention of cholestasis specifically in IF patients is limited and somewhat conflicting. In a recent randomized controlled trial, neonates receiving SMOF after gastrointestinal surgery did not have higher liver enzymes or incidence of cholestasis than neonates receiving a 50% soybean based emulsion [17]. Alternatively, in a randomized controlled trial of infants in China following intestinal surgery, infants receiving SMOF for 4 weeks had lower liver enzymes and direct bilirubin but no difference in weight gain or sepsis episodes compared to patients receiving a mediumchain triglyceride/long-chain triglyceride emulsion [18].…”
Section: Discussionmentioning
confidence: 96%
“…However, the added benefit of a reduction in cholestasis with FO in the PN regimen does not completely preclude the occurrence of IFALD. In fact, it has been documented that IFALD does occur, albeit less frequently, while using combination LEs such as SMOF [14,15]. In a previous study, we reported the incidence of IFALD to be 11.2% (28/251) among pediatric patients receiving PN containing SMOF for periods longer than 30 days and 12.3% in neonates [5].…”
Section: Discussionmentioning
confidence: 89%
“…In stable growing infants receiving enteral nutrition, laboratory monitoring every week or every other week is sufficient [17]. In those receiving prolonged parenteral nutrition, liver function should be monitored using serum levels of direct bilirubin, aspartate amino transferase, alanine amino transferase, alkaline phosphatase, gamma-glutamyl transpeptidase, and triglycerides [17,84,85].…”
Section: Biochemical Markersmentioning
confidence: 99%